THE CONDUCTOR AS NOT ONLY A LEADER, BUT ALSO A PEDAGOGUE: PSYCHOLOGICAL APPROACHES IN WORKING WITH AN ORCHESTRA - Abdurayimov Faxriddin Muxammadali o‘g‘li (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Annotation: This article explores the multifaceted role of the conductor in the context of orchestral education and performance. It highlights how the conductor serves not only as a musical leader but also as a pedagogical figure who shapes the emotional, psychological, and artistic development of ensemble members. The article emphasizes the importance of psychological insight, communication, empathy, and motivational strategies in achieving harmony, discipline, and high-level artistic expression within orchestral settings.